El futuro de Chile delineado en un mapa. - Sagredo Baeza, Rafael (Revista de Geografía Norte Grande, 2018)
Relating cartography to science and politics, the first map of republican Chile, delineated by Claudio Gay and commissioned by the State in the mid-1830s, is interpreted as the expression of an institutional project through which the organizers of the republic projected their work towards the future. In this context, the map is understood not only as a mean to shape and represent the territory, but above all, as a political instrument that anticipates the national reality that was shaped during the nineteenth century.